Examining the relationship between dysmorphia symptoms and suicidality through the lens of the Interpersonal Theory of Suicide. Issue 2 (21st August 2022) - Ortiz, Shelby N.; Grunewald, William; Morgan, Robert; Smith, April
Abstract: Objective: Using the Interpersonal Theory of Suicide (IPTS) as a framework, this two‐study investigation tested whether burdensomeness and low belongingness explained the association between body and muscle dysmorphia symptoms and suicidal ideation (tested in Study 1 and Study 2), and if fearlessness about death and pain tolerance explained the association between dysmorphia symptoms and previous suicide attempt frequency (tested in Study 2). Methods: Study 1 used a community sample ( n = 273) and Study 2 used an at‐risk population sample ( n = 261). Participants completed cross‐sectional questionnaires online. Results: In Study 1, both types of dysmorphic symptoms related to suicidal ideation through burdensomeness, but only body dysmorphic symptoms related to suicidal ideation through low belongingness. In Study 2, results were replicated as both types of dysmorphic symptoms related to suicidal ideation through burdensomeness. While both types of symptoms related to low belonging, low belonging did not relate to suicidal ideation. Neither dysmorphic symptoms nor capability for suicide related to frequency of suicide attempts. Conclusions: Results suggest that improving interpersonal needs, such as feeling more effective, may be important treatment targets for individuals with dysmorphic symptoms who also experience suicidal ideation. Future work should continue to identify mediators for suicide attempts among individuals with dysmorphia symptoms.